Non alcoholic fatty liver disease is a predictor of subclinical Carotid Atherosclerosis in the presence of Metabolic Syndrome - Kemaloglu, Cemal; Kemaloglu, Melek Didem (Nepalese Heart Journal, 2019)
Objective: The aim of this study is to identify the relationship between carotid intima-media thickness (c-imt) and non-alcoholic fatty liver disease (NAFLD), and to determine whether NAFLD is an independent predictor for the progression of atherosclerosis. Method: This is a prospective randomized controlled study. 103 NAFLD patients who have hepatosteatosis with grade II and above were enrolled in this study. Patients were divided into NAFLD with metabolic syndrome (MS) and NAFLD without MS groups and compared with 50 healthy people. Basal demographic characteristics and C-imt of all patients and control group were measured. Results: C-imt and carotid cross sectional area rates in the NAFLD groups were significantly higher than those in the control group. The mean and max. c-imt levels were significantly higher in the NAFLD group with metabolic syndrome (p<0,001). Homeostatic Model of Assessment-Insulin Resistance (HOMA-IR) levels were increased in the group with metabolic syndrome than those in the group without metabolic syndrome, with statistical significance (p<0.001). There was no difference in c-imt levels between HOMA-IR positive and negative groups (p=0.254) in patients with NAFLD and without metabolic syndrome. There was only a mild positive corelation between c-imt levels and high sensitive C-Reactive protein (hs-CRP) levels in metabolic syndrome positive group (p=0.026 r=0.30). Conclusion: NAFLD was a significant predictor to determine the increased risk of carotid atherosclerosis.